EFSA Workshop on in vitro comparative metabolism studies in regulatory pesticide risk assessment. Issue 4 (11th April 2019) - ,
Abstract : The European Union (EU) pesticides Regulation established that in vitro comparative metabolism studies shall be performed. At present an Organisation for Economic Co‐operation and Development (OECD) test guideline for this kind of studies is not available. The European Food Safety Authority (EFSA) Workshop on in vitro comparative metabolism studies in regulatory pesticide risk assessment discussed the use of these studies to identify human metabolites and to support the assessment of human relevance of chemical‐mediated thyroid disruption. Discussions focused on the minimum amount of information that should be provided to satisfy the data requirement and should be included in the study protocols, the key elements to be considered for the interpretation of the studies outcome and how metabolism data can be used in a weight of evidence (WoE) approach for endocrine mediated mechanisms of toxicity. From the Workshop it became clear that a guidance document is needed on how to conduct and interpret these studies for the identification of human metabolites. The workshop outcome can be the foundation stone for developing such guidance. For supporting the assessment of human relevance of chemical‐mediated thyroid disruption, the workshop outcome recommended that some mechanistic relevant key events should be measured to use this information as part of WoE approach.